Safeguards Assessments : 2006 Update. (Policy Papers; Policy Paper ;, 2006)
This paper provides Executive Directors with an update of safeguards assessment activities through the first half of 2006. This is the first update report following the review of the safeguards policy in April 2005, when Directors agreed that such reports should be prepared on an annual basis going forward rather than on a semi-annual basis.